HEMANGIOMA INFANTIL (PERDOSKI, 2022)
Infantile hemangiomas (IH) are the most common benign vascular tumors in infancy and childhood. Hemangiomas may be present at birth, but most develop in the ﬁrst few weeks after birth. Classification is used to differentiate the location of the lesion namely superficial, deep or mixed type. The pathogenesis of HI has not yet been fully explained. Although it is still under debate, it is concluded that placental angioblast embolic or intrinsic endothelial progenitor cells have the ability to proliferate clonal under the influence of appropriate cytokines. Infantile hemangiomas are distinguished from other vascular tumors and malformations by their unique growth pattern (rapid proliferative phase with subsequent slower involution. Studies have shown that in the proliferative phase, there is an imbalance of angiogenic and vasculogenic. As hemangioma could regress spontaneously, it generally does not require treatment unless proliferation interferes with normal function or gives rise to risk of serious disﬁgurement. Severe cases that require treatment are considered due to location or distribution, life threatening (subglottic, multifocal with visceral involvement), impaired function (periorificial), causing severe ulceration and bleeding (lumbosacral, genital) or risk of permanent disability (central facial, breast). Historic treatment options for IH include corticosteroids, beta blockers, surgery, lasers, or a combination of these therapies.